The Relationship Between Anemia and the Incidence of Premature Rupture of Membranes in Laboring Mothers - Nola Yusra; Siti Husaidah; Roza Erda (Jurnal Kesehatan Cendikia Jenius, 2025)
Premature rupture of membranes (PROM) in laboring mothers can lead to infections that contribute to the increased maternal mortality rate. Maternal death may occur during childbirth or shortly afterward. According to the Indonesian Health Survey, the incidence of PROM is 4.3%. Anemia is one of the factors that increases the risk of premature rupture of membranes. The purpose of this study is to analyze the relationship between anemia and the incidence of PROM in laboring mothers at Harapan Bunda Hospital, Batam City, in 2025. This research uses a quantitative method with a cross-sectional study design. The sampling technique used is simple random sampling with a total of 85 laboring mothers as respondents from January to May 2025 at Harapan Bunda Hospital, Batam City. The results of the chi-square analysis showed that there is a relationship between anemia and the incidence of premature rupture of membranes (PROM) in laboring mothers at Harapan Bunda Hospital, Batam City, as indicated by a p-value of 0.032 (α<0.05). There is a significant association between anemia and the occurrence of PROM. However, anemia is not the only contributing factor to PROM. Therefore, efforts to prevent PROM should be carried out comprehensively through monitoring hemoglobin levels, regular consumption of iron supplements, and providing health education during pregnancy.